Analisis Pelaksanaan Keuangan Desa Kayungo Sari Berdasarkan Permendagri Nomor 113 Tahun 2014 (Studi pada Desa Kayungo Sari Kecamatan Long Ikis Kabupaten Paser) - florentina iin ude; set asmapane; wulan sari (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
This research aims to find out the implementation of village finance at Kayungo Sari village Sub-district of Long Ikis District of Paser. This research using qualitative research. The data collection technique was conducted by using semi structure interviews. The research method used is a Creswell (2013). The result of the study are presented based on interview questions relating to implementation of village finance that have been reduced to coding. Based on the coding results, then can determined the theme. The results of this research indicate that implementation of village finance at Kayungo Sari village sub-district of Long Ikis District of Paser is in accordance with Permendagri Number 113 of 2014. Homever, there is still something that must be considered and reevaluated by the Kayungo Sari village government in retion to the principle of transparency namely the lack of transparency in the delivery of village financial resources and APBDes reports to the public.